The relation between cognitive dysfunction and diffusion tensor imaging parameters in traumatic brain injury. (23rd February 2019) - Hanks, Robin; Millis, Scott; Scott, Selena; Gattu, Ramtilak; O'Hara, Nolan B.; Haacke, Mark; Kou, Zhifeng
ABSTRACT: Purpose of the Study : To investigate the association among global and regional white matter fractional anisotropy (FA) values following traumatic brain injury (TBI) and cognitive functioning. Materials and Methods : This research was conducted in an urban rehabilitation hospital. Participants included adults who were healthy controls ( n = 18) or who had a TBI ( n = 27). Diffusion tensor imaging using a Siemens VERIO 3T scanner and calculation of global and regional FA values were undertaken. FA values were correlated with neuropsychological test scores and injury severity variables. Logistic regression and receiver operating characteristic (ROC) curve analysis were used to investigate discriminative ability of the FA values. Neuropsychological measures, including the Symbol Digit Modalities Test (SDMT), Trail Making Test, Wechsler Test of Adult Reading, California Verbal Learning Test 2nd Edition, Digit Vigilance Test, and Wisconsin Card Sorting Test, comprised the cognitive measures. Results : Within the TBI group, regional FA values were significantly lower across regions compared with controls; global FA and five brain regions were associated with SDMT scores. The FA value within the body of the corpus callosum (CC) yielded excellent discrimination between groups. Conclusions : Convergent findings support the discriminability and potential clinical utility of the CC body FA value in the context of TBI.